2023
DOI: 10.1002/ajoc.202300359
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies for the Construction of Indolizines and Indolizine‐fused Compounds: Thienoindolizines and Indolizinoindoles

Alisa A. Nevskaya,
Anna D. Zinoveva,
Erik V. Van der Eycken
et al.

Abstract: This paper provides a review on various methodologies developed for the synthesis of different indolizine derivatives and an overview of their application. These include thienoindolizine and indolizino[8,7‐b]indole derivatives. The indolizine nucleus occurs as privileged scaffold of many natural and synthetic molecules with significant biological activity. Fused‐indolizines such as thienoindolizines and indolizinoindole derivatives are of great interest, due to their antitumor, antimicrobial and enzyme inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Indolizinoindole derivatives have also shown significant biological activity, as evidenced by numerous publications. [18][19][20] The indolizino [8,7-b]indole skeleton has been found in natural bioactive substances, which possess notable analgesic, [21] antitumor, [22] and antibacterial [23] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indolizinoindole derivatives have also shown significant biological activity, as evidenced by numerous publications. [18][19][20] The indolizino [8,7-b]indole skeleton has been found in natural bioactive substances, which possess notable analgesic, [21] antitumor, [22] and antibacterial [23] effects.…”
Section: Introductionmentioning
confidence: 99%
“…27 Under metal-, external oxidant-, and base-free conditions, pyridine rings were conveniently fused with enaminones, affording diverse functionalized indolizines straightforwardly (Scheme 1c). 28,29 Although the preliminary mechanism investigation indicated that the in situ generated pyridine-Bpin radical (Py-Bpin˙) triggered the reaction, the underlying precise mechanisms, particularly those beyond the initial radical generation, remain elusive and amenable to address. For example, it has been well-known that Bpin˙ can migrate from pyridines to the carbonyl groups, affording OBpin-ligated ketyl radicals.…”
Section: Introductionmentioning
confidence: 99%